Attraction effect of different colored cards on thrips Frankliniella intonsa in cowpea greenhouses in China - Mao, Liangang (Sci Rep, 2018)
The flower thrips Frankliniella intonsa (Trybom) is one of the most economically important pests in cowpea greenhouses in China. Widespread pesticide resistance of thrips and the negative environmental effects limit the application of pesticides for thrips control. Two commercial cowpea greenhouse experiments were designed to determine the color preference of F. intonsa to colored cards, including white, pink, pale green, light yellow, powder blue, crimson, yellow green, deep sky blue, dark slate blue, dark orange, medium orchid, gold, and black. Clear pieces of plastic were used as the control cards. Additionally, the effects of placement height and orientation (cardinal direction) of the cards were also studied. Both greenhouse trials showed that white cards were significantly more attractive to F. intonsa than the other 13 card colors, followed by deep sky blue cards. White or deep sky blue cards placed low to the ground were found to be most attractive to F. intonsa. Orientation of the colored cards also affected the attractiveness to F. intonsa. The results indicate that white sticky cards were significantly more attractive to F. intonsa than blue cards and therefore can be recommended to monitor F. intonsa population densities and to control them in cowpea greenhouses as part of integrated pest management programs.